Postoperative intensive care unit stay after minimally invasive esophagectomy shows large hospital variation. Results from the Dutch Upper Gastrointestinal Cancer Audit. Issue 8 (August 2021) - Voeten, Daan M.; van der Werf, Leonie R.; Gisbertz, Suzanne S.; Ruurda, Jelle P.; van Berge Henegouwen, Mark I.; van Hillegersberg, Richard; van Det, Marc J.; van Duijvendijk, Peter; van Esser, Stijn; van Etten, Boudewijn; van der Harst, Erwin; et al.
Abstract: Introduction: The value of routine intensive care unit (ICU) admission after minimally invasive esophagectomy (MIE) has been questioned. This study aimed to investigate Dutch hospital variation regarding length of direct postoperative ICU stay, and the impact of this hospital variation on short-term surgical outcomes. Materials and methods: Patients registered in the Dutch Upper Gastrointestinal Cancer Audit (DUCA) undergoing curative MIE were included. Length of direct postoperative ICU stay was dichotomized around the national median into short ICU stay ( ≤ 1 day) and long ICU stay ( > 1 day). A case-mix corrected funnel plot based on multivariable logistic regression analyses investigated hospital variation. The impact of this hospital variation on short-term surgical outcomes was investigated using multilevel multivariable logistic regression analyses. Results: Between 2017 and 2019, 2110 patients from 16 hospitals were included. Median length of postoperative ICU stay was 1 day [hospital variation: 0–4]. The percentage of short ICU stay ranged from 0 to 91% among hospitals. Corrected for case-mix, 7 hospitals had statistically significantly higher short ICU stay rates and 6 hospitals had lower rates. ICU readmission, in-hospital/30-day mortality, failure to rescue, postoperative pneumonia, cardiac complications and anastomotic leakage were not associated with hospital variation in length of ICU stay. Total length of hospital stay was significantly shorter in hospitals with relatively short ICU stay. Conclusion: This study showed significant hospital variation in postoperative length of ICU stay after MIE. Short ICU stay was associated with shorter overall hospital admission and did not negatively impact short-term surgical outcomes. More selected use of ICU resources could result in a national significant cost reduction. HIGHLIGHTS: Hospital variation exists in length of ICU stay after minimally invasive esophagectomy It ranges from a median of 0–4 days among hospitals The hospital variation in length of ICU stay does not impact surgical outcomes Total length of hospital stay is shorter after a short ICU stay